Pathologic Tooth Migration-Spontaneous Repositioning Following a Non-Surgical Periodontal Therapy: A Case Report - Punit Vaibhav Patel (Journal of Clinical and Diagnostic Research, 2013)
This case report describes the spontaneous correction of a pathologic tooth migration (PTM) and reduced infra-bony pockets after a nonsurgical periodontal therapy.